Microstructure and Optical Properties Study of Nd-doped BiFeO3 (Ba1-xNdxFeO3) Films on Quartz Substrate - Iriani, Yofentina; Sandi, Dianisa Khoirum; Nurmawanti, Rainisa; Budiawanti, Sri; Agustina, Elvinda Bendra (Universitas Negeri Surabaya, 2021)
Bismuth ferrite oxide (BFO), due to its remarkable properties, has become one of the most attractive multiferroic materials to be extensively studied. BFO doped with various materials, including Neodymium (Nd), could improve its properties that apply to numerous electronic devices. However, the studies related to the properties of Nd-doped BFO (Ba1-xNdxFeO3) thin films on a quartz substrate, especially the optical properties, are relatively scarce. This study aimed to investigate the microstructure and optical properties of the Nd-doped BFO (BNFO) as the variation of the Nd concentrations. The BNFO thin films with Nd concentrations of 0.05 (BNFO5); 0.1 (BNFO10); and 0.2 (BNFO20) have been deposited on the quartz substrates via the sol-gel method and using spin coating. The films were annealed at 600 °C for 1.5 h. The XRD result of the BNFO films revealed a single phase of BFO with a cubic structure. The lattice constants and volume cells of the films declined with more Nd. Meanwhile, the crystallite size and lattice strain changed due to the change in the Nd number. Additionally, the morphology images showed the pores on the films’ surface and the different film thicknesses of each BNFO film. From the optical characterization, the transmittance spectra of the BNFO films tended to rise as the more Nd amount doped, in which the BNFO20 had the highest transmittance. The BNFO10 had the highest refractive index, followed by the BNFO5 and BNFO20. Contrarily, the BNFO20 had the highest extinction coefficient and spectra, followed by the BNFO5 and BNFO10. Further, the bandgap values of the BNFO5, BNFO10, and BNFO20 were 2.75, 2.85, and 2.64 eV, respectively. Accordingly, due to the highest Nd amount that most impacted its microstructure, the BNFO20 exhibited the lowest bandgap value compared to the other films that are good for photovoltaic applications.